2017
DOI: 10.1007/s00586-017-5018-6
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of the coronal plane deformity in Parkinson disease

Abstract: The present study indicated that the postural deformities in the coronal plane were related to the morphology of the spinal level, especially the position of the Cobb angle. To benefit the PD patients with PS, the full-length standing spine radiographs should be performed as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
2
18
1
2
Order By: Relevance
“…Currently, the Cobb angle is an objective radiographic parameter to quantify the severity of scoliosis on coronal radiographs [4]. A Cobb angle > 10° is considered clinically significant for scoliosis diagnosis [5], whereas the variability of Cobb angle measurements has been reported to range from 3° to 10° in previous studies [6]. In addition, manual measurement is time-consuming, especially in scoliosis screening.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Cobb angle is an objective radiographic parameter to quantify the severity of scoliosis on coronal radiographs [4]. A Cobb angle > 10° is considered clinically significant for scoliosis diagnosis [5], whereas the variability of Cobb angle measurements has been reported to range from 3° to 10° in previous studies [6]. In addition, manual measurement is time-consuming, especially in scoliosis screening.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, Parkinson's disease was associated with a higher incidence of scoliosis in women. There was also a positive relationship between the severity of PD symptoms and the extent of scoliosis [27,28]. In my other studies, research was conducted in the area of postural stability analysis among PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, PD causes postural disorder, such as anterocollis, Pisa syndrome, and camptocormia [2][3][4][5]. Reports have shown that these postural abnormalities increase susceptibility to rigid spinal deformities [2,3] and that patients with PD develop adult spinal deformity (ASD) more frequently than the general population in the same age groups [6].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, PD causes postural disorder, such as anterocollis, Pisa syndrome, and camptocormia [2][3][4][5]. Reports have shown that these postural abnormalities increase susceptibility to rigid spinal deformities [2,3] and that patients with PD develop adult spinal deformity (ASD) more frequently than the general population in the same age groups [6].Recent studies have shown that ASD negatively affects health-related quality of life [7,8]. Surgical 4 treatment has been shown to provide better health-related quality of life outcomes than non-surgical treatment, especially in patients with severe deformity [9].…”
mentioning
confidence: 99%